Development of fast disintegrating tablet formula of ketoprofen-β-cyclodextrin inclusion complexes - Rachmawati, Heni; Marbun, Estherina Juliana; Pamudji, Jessie S. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Ketoprofen is one of non steroidal anti inflammatory drugs (NSAID) used for rheumatoid arthritis. However, unpleasant taste of ketoprofen leads to difficulty in the formulation, in particular for oral route. Therefore, in present study, a technique to mask the unacceptable taste of ketoprofen was developed. Then, a fast disintegrating tablet on this inclusion complex was established for rapid release and faster analgesic effect of ketoprofen. Taste masking was prepared by complex inclusion with β-cyclodextrin. The ratio of ketoprofen and β-cyclodextrin was varied. The fast disintegrating tablet was formulated with direct compression using various ratios of mannitoland lactose as tablet diluent, the main factor influencing the successful of fast disintegrating tablet. Evaluation of final product was performed according to compendial standard and specific requirements for fast disintegrating tablet. The best ratio from ketoprofen and β-cyclodextrin was 2:3 with concentration of ketoprofen in inclusion complex was 40.32%. The tablet met standard requirement was resulted with the composition of ketoprofen-cyclodextrin equivalent to 50 mg of pure ketoprofen and mannitol and lactose (ratio 1:1) as tablet diluent. Fast disintegrating tablet of modified ketoprofen in inclusion complex was fulfilled standard specification for ketoprofen tablet with better acceptance.Key words:ketoprofen, inclusion complex, fast disintegratingtablet, beta cyclodextrin.